Risk Indicator To Estimate The Potential In Business - Abdul Hadi, Anis Aniza; Ghazali, Puspa Liza; Foziah, Nik Hazimi Mohamad; Ismail, Izzat; Zain, Eni Noreni Mohamad (Asean International Journal of Business, 2022)
Purpose – This paper is to review the comparison of risk indicator in order to estimate the potential in business. While solving the challenges of budgetary wealth distribution in a work plan, the judgement might consider of not just the profitability and cost of the project, and perhaps its sustainable development. Methodology/approach – Our main contribution to this literature is to make the comparison of the results in previous research study for risk of indicator. Findings – The globe is facing severe ecological and sustainability difficulties as a result of the country's rapid urbanisation, depletion of natural resources, and the fight against climate change. As a result, there is a lot of hope in the notion of company improvement. The index was built utilising multi-criteria decision-making techniques. A development's synthesis impact assessment, which incorporates all of these characteristics, may indeed be helpful in analyzing the long-term viability of a company task and make judgments about construction management diversification and economic capital allocation. Novelty/value – While solving the challenges of budgetary wealth distribution in a work plan, the judgement might consider of not just the profitability and cost of the project, and perhaps its sustainable development. This study's insight should assist enterprises to actualize potential in business, which may also contribute to the long-term growth of organisations and so strengthen their competitive strength.